2018
DOI: 10.1038/s41598-018-29175-2
|View full text |Cite
|
Sign up to set email alerts
|

Attachment ability of the polyphagous bug Nezara viridula (Heteroptera: Pentatomidae) to different host plant surfaces

Abstract: The present investigation tests through friction experiments the attachment ability of adults of the southern green stink bug Nezara viridula L. (Heteroptera: Pentatomidae), a polyphagous insect representing a cosmopolitan pest, on different host plant species characterized by smooth, hairy and waxy surfaces. Surfaces of different tested plants have been studied in Cryo-Scanning Electron Microscope (Cryo-SEM). The load cell force transducer was used to evaluate the potential damage to the insect attachment dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
46
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 44 publications
(46 citation statements)
references
References 44 publications
0
46
0
Order By: Relevance
“…; Salerno et al . ). Nevertheless, the series of recent studies on stink bug attachment on flat surfaces widely neglected the preferred curved plant substrates and related biological particularities of N. viridula in the context of the current state of knowledge on insect attachment.…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…; Salerno et al . ). Nevertheless, the series of recent studies on stink bug attachment on flat surfaces widely neglected the preferred curved plant substrates and related biological particularities of N. viridula in the context of the current state of knowledge on insect attachment.…”
Section: Introductionmentioning
confidence: 97%
“…Recent studies have shown the attachment ability of adult N. viridula to various leaf surfaces and hydrophilic (water attractive) glass, as well as smooth and rough hydrophobic (water repellent) epoxy resin (Salerno et al . , ,b; Voigt et al . ; see notes below Table S1 for explanation of surface wettability).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our experiments, the safety factor values of B. oleae obtained on glass at the beginning and at the end of each set of tests with olives were not significantly different. Similarly, in force experiments with the beetle Chrysolina fastuosa (Scopoli) (Coleoptera: Chrysomelidae) [42], with the aphid Acyrthosiphon pisum Harris (Hemiptera: Aphididae) [43] and with the bug Nezara viridula L. (Hemiptera: Pentatomidae) [44] on plant species with EWs, no influence of the waxy surfaces on the subsequent insect attachment ability was observed, or recovery of the attachment ability occurred rather quickly. Therefore, we can exclude that one of the main reasons of the reduction in B. oleae attachment to the olive surface could be linked to contamination of insect adhesive pads with broken fragments of wax projections, as demonstrated previously for several insect species with the hairy type of pads, such as Adalia bipunctata (L.) (Coleoptera: Coccinellidae) [45] or C. fastuosa [46].…”
Section: Ews Effect On the Attachment Ability Of Bactrocera Oleae To mentioning
confidence: 99%
“…The reduction of insect adhesion of B. oleae could be linked better to the roughness hypothesis [42,47], stating that wax projections reduce insect adhesion owing to the surface microroughness, similar to the effect of microrough polishing paper with 0.3-1.0 µm asperity sizes minimizing insect pad contact areas due to small surface irregularities. Such a reduction has been demonstrated in many different insect species [44,[48][49][50][51][52][53][54][55], among which the Mediterranean fruit fly C. capitata [32].…”
Section: Ews Effect On the Attachment Ability Of Bactrocera Oleae To mentioning
confidence: 99%